Detecting Deepfake images using deep convolutional neural network - Dhar, Arpita; Acharjee, Prima; Biswas, Likhan; Ahmed, Shemonti; Sultana, Abida (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.